Belajar Perkalian dengan Menggunakan Metode Jarimatika Untuk Anak Usia SD Desa Alaang, Kabupaten Alor - Jeni Marianti Loban; Narita Yuri Adrianingsih; Landerius Maro; Martasiana Karbeka (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Counting for some children is a difficult and boring activity, this has an impact on children's interest in mathematics is low. Therefore it is necessary to make efforts to increase children's interest in mathematics. A creative, innovative and interactive and fun learning process can increase children's interest and ability towards mathematics. Besides that, fun counting activities can increase a love for mathematics and counting, this is the goal of this community service activity. Multiplication by using the jarimatics method can help students more easily understand and remember multiplication one (1) to nine (9). The target of this service is all elementary school-age children in Alaang Village, Alor Barat Laut District, Alor Regency-NTT. These activities can run with the support of the Alaang Village government and all the community, our learning activities are carried out in the open, namely the shores of Alaang beach, with the concept of learning while playing. The enthusiasm of the children was high and they were interested in and really enjoyed the process of learning to count multiplication with fingers.Keywords: Calculate Multiplication, Jarimatika method.